Anti-lung Cancer and Anti-angiogenic Activities of New Designed Boronated Phenylalanine Metal Complexes - Varol, Mehmet; Koparal, Ayse T.; Benkli, Kadriye; Bostancioglu, Rakibe Beklem (Current Drug Delivery, 2018)
Background: Drug design and discovery studies still remain of great importance in the search for more convenient chemotherapeutic to avoid the drug resistance, systemic toxicity or the longterm side effects. Objective: A series of mononuclear gold (III) and platinum (II) complexes based on 4-dihydroxyboryl- DL-phenylalanine (BPA) was designed and synthesized, for the first time, by using 2, 2'-dipyridyl (L1) and 4, 4'-diaminobibenzyl (L2) ligands. Characterization of the synthesized complexes was achieved by using 1H-NMR, IR, MS and elemental analyses. Method: MTT cell viability, endothelial tube formation, cancer cell colony formation and TRITCphalloidin cytoskeleton staining assays were performed on human umbilical vein endothelial (HUVEC) and human lung adenocarcinoma (A549) cells to establish the anticancer and anti-angiogenic activities of the complexes. It was determined that the organometallic complexes that include 2, 2'-dipyridyl ligand have higher antiproliferative activity than L2-based complexes in the micromolar range. Colony formation experiments showed that the anchorage-independent growth ability of A549s was significantly affected by the complexes in a concentration-dependent manner though L1-based complexes were more effective than L2-based ones. Results: It was also clearly observed that the complexes have significant anti-angiogenic and cytoskeleton alterative activities. Consequently, the phenylalanine-based organometallic complexes seem to have anti-lung cancer and anti-angiogenic activities depending on the ligand type and a great potential in oncology drug development because phenylalanine amino acid has an ability to cross the cell membrane by using L-amino acid transport system. Conclusion: Design, synthesis and activity studies with amino acid analogs should be therefore increased to discover more efficient drugs to cure cancer diseases.
Keywords: cisplatin